Formamide-based prebiotic chemistry in the Phlegrean Fields. Issue 8 (15th October 2018) - Botta, Lorenzo; Saladino, Raffaele; Bizzarri, Bruno M.; Cobucci-Ponzano, Beatrice; Iacono, Roberta; Avino, Rosario; Caliro, Stefano; Carandente, Antonio; Lorenzini, Fabio; Tortora, Alessandra; Di Mauro, Ernesto; Moracci, Marco
Highlights: One-pot synthesis of nucleobases and carboxylic acids. Hydrothermal fields as shrine for prebiotic chemistry. Formamide as general precursor of biomolecules. Abstract: Understanding the formation of biogenic molecules in abiotic conditions is a prerequisite in the origin-of-life studies. Determining the conditions allowing an efficient one-pot synthesis of the largest possible panel of biogenic compounds may shed light on the plausible scenario in which the processes that kick-started life might have occurred. We report a set of experiments describing the syntheses taking place from formamide (NH2 CHO) and thermal water in the presence of meteorites, in the hydrothermal physical-chemical environment of the Phlegrean Fields. The results show that meteorites catalyse the synthesis of a large panel of organic compounds of biological relevance, including carboxylic acids, nucleobases, amino acids and sugars. The simplicity of the system (a one-carbon molecule as starting compound, a volcanic hydrothermal environment, meteorites as catalysts) hints to a possible extension of the results to similar environments present in other planetary bodies and space objects.